The Role of Leadership and Community Involvement in Sustainable Development - Dicky Hida Syahchari; Erik Van Zanten (Bina Nusantara University, 2024)
Indonesia is an archipelagic nation that has a variety of difficulties when it comes to the delivery of products and services. There are a number of challenges experienced in the field of logistics in Indonesia, including poor transportation infrastructure in a number of different places. Sustainable development is a concept that aims to find a balance between peopleâ€™s needs now and their ability to meet those needs in the future. The research aimed to identify and analyze the relationship between leadership and community involvement (also known as community participation or engagement) in sustainable development in the shipping industry. The research used the Partial Least Squares-Structural Equation Model (PLS-SEM) with a sample of 103 shipping companies to analyze data. The research results show that leadership positively and significantly impacts sustainable development, confirming the importance of the leaderâ€™s role in implementing sustainable practices in company operations. Meanwhile, community involvement Â shows a positive but insignificant impact on sustainable development, indicating that the community needs to be reconsidered in the context of sustainable development in the shipping industry. The results also provide information for companies and leaders to strengthen sustainable development efforts by implementing more integrated policies focused on community involvement. Moreover, the research offers a chance to encourage cooperation between industrial actors and local populations. By harmonizing objectives, expectations, and actions, it is feasible to develop projects that strengthen sustainable practices within the ocean freight transportation business and promote the well-being of the communities it interacts with.